APPLICATION OF MANAGEMENT ACCOUNTING INFORMATION IN DECISION MAKING AT THE AGRICULTURE AND LIVESTOCK DEPARTMENT OF KETAPANG DISTRICT - Hery Medianto Kurniawan (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
Good decisions can be generated by the leadership at every level of management at the Department of Agriculture and khsusnya Peternakan Kabupaten Ketapang, if the available information that is efficient, precise and direct. How does an information presented to the leaders of it depends on the good and bad sisitem management information from the company. In the selection of the proposed decision, the management at the Department of Agriculture and Veterinary Office diferenssial Ketapang require accounting information as one important basis for determining the selection decision. Diferrensial accounting information is incorporated into a model of decision making in the form of assessment methods to allow the management of the Department of Agriculture and Livestock of Ketapang choose keputusanterbaik. Based on the above, and considering the importance of management accounting information systems at the Department of Agriculture and Livestock of Ketapang in decision making. Based on the background of the issues outlined above, it can be the problem as follows if the Department of Agriculture and Livestock of Ketapang been using management accounting information as a basis for decision making? How is the effectiveness of management accounting information in decision making at the Department of Agriculture and Livestock of Ketapang?From other research goal should be concluded that the management accounting information in decision making at the District Agricultural Office Ketapang very effectively used to assist management in decision-making among the existing alternatives. This can be seen by the following reasons: Ketapang District Agriculture Office is fully aware of the importance of management accounting reports that will help the decision, whether long-term decisions, short-term, routine decisions or for the purpose of internal control. Ketapang District Agriculture Office in making investment decisions with regard to budget management and accountability are the differential management accounting information.